Mechanical properties of lightweight aggregate concrete containing unground palm oil fuel ash as partial sand replacement - H. Mohd, Hanafi; Khairunisa, Muthusamy; Wan Ahmad, Saffuan; Budiea, Ahmed Mokhtar Albshir; Kusbiantoro, Andri; Nabilla, Mohamad; Rafiza, Abdul Rahman; Błoch, Katarzyna (Polska Akademia Nauk, 2024)
Escalating quantity of industrial by-products generated, including oil palm shell (OPS) and palm oil fuel ash (POFA) of the palm oil industries, has been a concern to many analysts. They are mostly disposed off as wastes that would heavily impact the environment quality. Therefore, this paper aimed to investigate the possibility of consuming these wastes by using OPS and POFA as replacement materials for fine aggregates in the concrete mixture. The mixtures were prepared by integrating unground palm oil fuel ash of 0%, 10%, and 20% (by weight of sand) to produce lightweight concrete. The experiments observed the mechanical performance of these specimens for 180 curing days. The results show the enhancement of concrete strength relative to the control mixture by using 10% of ash. This is owing to void filling mechanism and product of pozzolanic reaction due to the fine particles of the ash.